Effect of 6 months hybrid closed-loop insulin delivery in young people with type 1 diabetes: a randomised controlled trial protocol. Issue 8 (13th August 2018) - de Bock, Martin; McAuley, Sybil A; Abraham, Mary Binsu; Smith, Grant; Nicholas, Jennifer; Ambler, Geoff R; Cameron, Fergus J; Fairchild, Jan M; King, Bruce R; Geelhoed, Elizabeth A; Davis, Elizabeth A; O'Neal, David Norman; et al.
Abstract : Introduction: Automated insulin delivery (also known as closed loop, or artificial pancreas) has shown potential to improve glycaemic control and quality of life in people with type 1 diabetes (T1D). Automated insulin delivery devices incorporate an insulin pump with continuous glucose monitoring(CGM) and an algorithm, and adjust insulin in real time. This study aims to establish the safety and efficacy of a hybrid closed-loop (HCL) system in a long-term outpatient trial in people with T1D aged 12 –<25 years of age, and compare outcomes with standard therapy for T1D as used in the contemporary community. Methods and analysis: This is an open-label, multicentre, 6-month, randomised controlled home trial to test the MiniMed Medtronic 670G system (HCL) in people with T1D aged 12 –<25 years, and compare it to standard care (multiple daily injections or continuous subcutaneous insulin infusion (CSII), with or without CGM). Following a run-in period including diabetes and carbohydrate counting education, dosage optimisation and baseline glucose control data collection, participants are randomised to either HCL or to continue on their current treatment regimen. The primary aim of the study is to compare the proportion of time spent in target sensor glucose range (3.9–10.0 mmol/L) on HCL versus standard therapy. Secondary aims include a range of glucose control parameters, psychosocial measures, health economic measures, biomarker status, user/technology interactions and healthcare professional expectations. Analysis will be intention to treat. A study in adults with an aligned design is being conducted in parallel to this trial. Ethics and dissemination: Ethics committee permissions were gained from respective institutional review boards. The findings of the study will provide high-quality evidence on the role of HCL in clinical practice.